The Vitamin D Gamble - Webster, Andrew L.H.. (The Meducator, 2012)
Studies have shown that most Canadians are deficient in Vitamin D3. In addition to its role in systemic calcium regulation, Vitamin D3 is also proposed to be integral to the suppression of cancer, as well as to the regulation of certain immune and endocrine components. Many experts are seriously concerned that Health Canada’s current Vitamin D3 dosage recommendations are inadequate to facilitate these mechanisms. A bitter debate on dosage has ensued—largely between researchers and regulatory bodies such as Health Canada and the US Institute of Medicine—leaving health practitioners caught in the middle with contradictory directives and information.